An evaluation of the religious education program of Lourdes School, Quezon City - Feniz, Agapito M. (Animo Repository, 1989)
Main Problem: The study was an attempt to make an evaluation of the religious education program of Lourdes School Quezon City. Specifically, it sought to obtain answers to the following questions: A. Context evaluation: 1. Based on the assessment of the principal, religion coordinator and religion teachers, to what extent are the goals and objectives of the religious education program of Lourdes School of Quezon City congruent with the: 1.1 National Catechetical Directory of the Philippines 1.2 Encyclical of the Church 1.3 Mission Statement of Lourdes School Quezon City. B. Input evaluation: 1. What is the profile of the high school teachers of religion in terms of: 1.1 educational training in religious studies 1.2 years of experience in teaching religion 2. Based on the assessment of the religion teachers how adequate are the school's facilities and instructional materials in attaining the religious education goals and objectives. C. Process evaluation: 1. How effective are the high school religion teachers of Lourdes School of Quezon city as assessed by the: 1.1 principal 1.2 religion coordinator 2. What are some of the problem and difficulties met by the religion teachers and religion coordinator? 3. To what extent do the extra-class activities strengthen the religious practices and attitudes of the students? D. Product Evaluation: 1. To what extent have the program objectives been achieved as assessed by the: 1.1 principal 1.2 religion coordinator 1.3 religion teachers 2. What are the terminal religious knowledge and attitudes of the senior students of Lourdes School of Quezon City? Treatment of Data: Item means, standard deviations, frequencies, percentages and ranks were used to present and analyze the data gathered from the survey instruments. Important findings of the study: 1. Context evaluation: The school principal, religion coordinator and the religion teachers are in agreement in saying that the goals and objectives of the religious education program of Lourdes School Quezon City are in congruent with: 1.1 the goals and objectives of religious education program of National Catechetical Directory of the Philippines 1.2 the goals as spelled our in the Vatican II encyclicals 1.3 the school's mission statement. 2. Input evaluation: 2.1 The average age of the religion teachers is 26 years old. The two male teachers are graduate of philosophy and are ex-seminarians, with no formal training in religious instruction. In contrast the two female religion teachers are holders of degree in education, one is pursuing a masteral degree in religious education. The average years of teaching religion is five years 2.2 In terms of adequacy of facilities and instructional materials, the respondents (religion coordinator and religion teachers) are partly dissatisfied with the present instructional and reading materials of the religious education program. They say that there is a need to procure contemporary and relevant reading and instructional materials to update the teachers and students on the latest trends and issues on religious educational development. Process evaluation: 3.1 As assessed by the principal and the religion coordinator, the religion teachers were satisfactory or very effective in the role as main vehicles for imparting the school's religious education program to students via instruction.